2021
DOI: 10.1136/jclinpath-2021-207426
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphatasia

Abstract: Hypophosphatasia (HPP) is a group of inherited disorders characterised by the impaired mineralisation of bones and/or teeth and low serum alkaline phosphatase (ALP) activity. It is caused by a mutation in the ALPL gene encoding the tissue-non-specific isoenzyme of ALP (TNSALP) resulting in a loss of function. The disease is highly heterogenous in its clinical expression ranging from stillbirth without mineralised bone to the mild form of late adult onset with symptoms and signs such as musculoskeletal pain, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 58 publications
0
12
0
1
Order By: Relevance
“…The manifestations of HPP in children cover a broad spectrum of severity but are also classified as discrete clinical subtypes (21). In the most severe forms of the perinatal lethal subtype, children who survive childbirth are born with skeletal hypomineralization and typically succumb to respiratory failure (19).…”
Section: Primary Metabolic Bone Disorders 21 Hypophosphatasiamentioning
confidence: 99%
“…The manifestations of HPP in children cover a broad spectrum of severity but are also classified as discrete clinical subtypes (21). In the most severe forms of the perinatal lethal subtype, children who survive childbirth are born with skeletal hypomineralization and typically succumb to respiratory failure (19).…”
Section: Primary Metabolic Bone Disorders 21 Hypophosphatasiamentioning
confidence: 99%
“…There is high allelic heterogeneity and can be inherited in an autosomal dominant or recessive pattern. 17,29 -31…”
Section: Inherited Dental Conditionsmentioning
confidence: 99%
“…showed that, the estimated prevalence of mild HPP could be double that of previously reported estimation for Spanish population (1/3,100 vs. 1/6,370), and there could be more than 15,000 potential patients affected with mild forms of HPP underdiagnosed due to a lack of recognition in clinical practice ( 3 ). The clinical manifestations and prevalence of HPP has changed significantly between 1997 and 2019 from a rare and mostly recessive bone disease to a multisystemic, mostly dominant and frequent disease in its moderate and mild form ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the ALPI, ALPP, ALPPL2 and ALPL genes encode intestinal (IALP), placental (PALP), tissue-specific germ cell (GCALP) and non-tissue-specific (TNSALP) ALP isoenzymes, respectively ( 4 ). The role of ALP is to hydrolyze phosphomonoesters with the release of inorganic phosphate ( 5 ).…”
Section: Introductionmentioning
confidence: 99%